(untitled) (Research, Society and Development, 2021)
The aim of the present work was to assess the biological viability of two titanium surfaces treated by electric discharge machining (EDM) using water or hydroxyapatite as modifying agents and compare them to a machined titanium surface without modifying agent as a control. The in vitro MTT, total protein, alkaline phosphatase and alizarin red assays and scanning electron microscopy were applied to analyze pre-osteoblastic MC3T3-E1 cells after 7, 14 and 21 days of cell culture on the titanium surfaces. The results showed the presence of cellular activity in all surfaces and the formation of bone matrix, with no discrepancy among the groups. All tested surfaces were capable of inducing bone formation. In the topographic analysis of the surface, EDM failed to modify the surface of the discs homogeneously. Thus, EDM is a low-cost, biocompatible technique that favors osseointegration, but which still needs to be improved.